MODEL KESESUAIAN LAHAN BERBASIS KERAWANAN BENCANA ALAM, UJI COBA: KOTA SEMARANG - Imam Buchori; Yuwono Ario Nugroho; Joko Susilo; Dian Prasetyaning; Hadi Nugroho (Diponegoro University, 2013)
Indonesian regions are prone to natural disasters. For this, Law 26/2007 on Spatial Planning orders that disaster mitigation is an important. This paper aims at developing a spatial model for suitability analysis, mainly considering physical and disaster prone conditions. The model is a raster based-GIS weighted scoring model. The model is applied in Semarang City with the consideration has various topographical conditions, from flat in the North and hilly in the South.The application shows that the model is suitable in representing land suitability in three categories, i.e. low, medium, and high flexibility of development. The validation, done by comparing the model output and reality, shows that its accuracy is 91,25%. However, to be widely generazed, the model needs to be tested more, by applying in other locations having criteria regardingthe needs of the test.